(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
One of the important environmental issues that modern technology has focused on due to its enormous effect on human health is the quality of the air that is inhaled. It is necessary and important for every human being to live in a healthy environment, whether inside or outside the house. However, pollution occurs everywhere, and most people’s attention and focus are on outdoor air quality while ignoring indoor air quality which is a critical factor that must be systematically assessed and analyzed to determine the air that humans breathe. In this work, a system was built to measure indoor air pollution. This system was equipped with several gas sensors, such as the MQ-2 sensor for carbon monoxide, the MQ-9 for natural gas, and the MQ-135 for carbon dioxide, in addition to the suspended particulate matter sensor (PM 2.5 and PM 10) to determine the pollution limit inside buildings. The system also provides a simplified solution that allows users to monitor indoor air quality in real-time and with time, pollutant concentrations might be measured, and close-by users will be informed of the danger level of certain harmful air pollutants via text message or call using the Global System for Mobile Communications (GSM).